Using Client Reminders to Increase Colorectal Cancer Screening in Montana, 2012 - Troyer, Lisa (Centers for Disease Control and Prevention, 2014)
BACKGROUND: Colorectal cancer (CRC) is the third leading cause of cancer death for men and women in the United States. CRC screening can save lives by detecting precancerous polyps that are then removed or by detecting cancer early when treatment is most effective. COMMUNITY CONTEXT: CRC screening participation in Montana is low. To increase screening participation among Montanans with health insurance, the Montana Cancer Control Programs (MCCP) partnered with a small association health organization (AHO). This partnership implemented a postcard campaign to increase CRC screening participation among the AHO’s enrollees. METHODS: Postcards were sent to 1,011 people insured through the AHO; 504 people were mailed 1 postcard and 507 people were mailed 2 postcards. Evaluation of the campaign assessed recall of the campaign among people who received 1 postcard versus people who received 2 postcards. OUTCOME: Women were 60% more likely to recall receiving the postcards than were men. People who received 2 postcards were 2.3 times as likely to recall receiving them as were people who received 1 postcard. INTERPRETATION: The MCCP considers this collaborative project with an AHO a promising approach to implementing evidence-based colorectal cancer screening interventions. The MCCP plans to partner with additional AHOs in Montana to evaluate CRC screening participation among their enrollees.